2012
DOI: 10.7897/2277-4343.03532
|View full text |Cite
|
Sign up to set email alerts
|

Ayurvastra: Herbal Couture Technology in Textile

Abstract: ABSTRCTAyurvastra is a branch of India's ancient form of medicine, Ayurveda. Ayurvastra cloth is used by Ayurveda health clinics in the treatment of a broad range of diseases such as diabetes, skin infections, eczema, psoriasis, hypertension, high blood pressure, asthma, arthritis, rheumatism, cardiac problems and as general health products. The Ayurvastra reinforces the importance of sustaining the planet for future generations and for the well being of the current generation using age old practices, which do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The principle of Ayurvastra is employed for well-being and to embrace a wholesome lifestyle. Regular use of natural organic fabrics dyed with natural chemical-free dyes would help yoga practitioners to establish equilibrium within the body's systems and strengthen the immune system [8].…”
Section: Introductionmentioning
confidence: 99%
“…The principle of Ayurvastra is employed for well-being and to embrace a wholesome lifestyle. Regular use of natural organic fabrics dyed with natural chemical-free dyes would help yoga practitioners to establish equilibrium within the body's systems and strengthen the immune system [8].…”
Section: Introductionmentioning
confidence: 99%
“…At present, little information in this aspect is available. [15][16][17][18] Natural dyes are being considered as a more environmentally friendly substitute for synthetic dyes but these have few draw backs low colourfastness property is one. But no study reported on improving the colourfastness properties of natural dyes with a natural dye fixing agents.…”
Section: Introductionmentioning
confidence: 99%